2005
DOI: 10.1159/000086064
|View full text |Cite
|
Sign up to set email alerts
|

Association of Amino Acid Substitution Pattern in Core Protein of Hepatitis C Virus Genotype 1b High Viral Load and Non-Virological Response to Interferon-Ribavirin Combination Therapy

Abstract: Objective: Patients with high titer (≧100 kIU/ml) of hepatitis C virus (HCV) genotype 1b do not achieve highly sustained virological response rates to combination therapy with interferon plus ribavirin. Non-virological responders (NVRs, namely ultimate resistant cases) who do not achieve HCV-RNA negativity during treatment are also encountered. We investigated the pretreatment virological features of NVRs. Methods: We evaluated 50 consecutive Japanese adults with high titer of HCV genotype 1b who received comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
297
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 257 publications
(311 citation statements)
references
References 75 publications
10
297
4
Order By: Relevance
“…The result shows that patients with mutant type of core aa 70 have the possibility of getting SVR. Several authors have reported that virus clearance in combination therapy of peginterferon-alpha and ribavirin is associated with HCV mutations in the core region and IL-28B (21)(22)(23)(24)(25)(26). The present study confirmed that IL-28B was related with SVR for HCV patients with genotype 1b and high virus load.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The result shows that patients with mutant type of core aa 70 have the possibility of getting SVR. Several authors have reported that virus clearance in combination therapy of peginterferon-alpha and ribavirin is associated with HCV mutations in the core region and IL-28B (21)(22)(23)(24)(25)(26). The present study confirmed that IL-28B was related with SVR for HCV patients with genotype 1b and high virus load.…”
Section: Discussionsupporting
confidence: 86%
“…HCV-genotype was examined by polymerized chain reaction assay, using a mixture of primers for the six subtypes known to exist in Japan, as reported previously (20). The core protein of HCV-1b was determined by the previous report (21). Next, the genetic variations near the IL28B gene (rs8099917), reported as the pretreatment predictors of treatment efficacy and clinical outcome, were investigated (22)(23)(24)(25)(26).…”
Section: Laboratory Investigationmentioning
confidence: 99%
“…Especially, substitutions of arginine (R) by glutamine (Q) at aa 70, and/or leucine (L) by methionine (M) at aa 91 were significantly more common in virological nonresponders. Decline of HCV-RNA levels during treatment in patients with specific substitutions in the core region was significantly less than in those without such substitutions [Akuta et al, 2005b].…”
Section: Introductionmentioning
confidence: 75%
“…Virological non-responders who could not or could achieve a log decline of more than 2 from baseline of HCV RNA based on quantitative PCR analyses during the initial 24 weeks of combination therapy, were defined as absolute virological non-responders or relative virological non-responders, respectively. Applying multivariate analysis, previous studies identified substitutions of aa 70 in the core region and substitutions of aa 91 as independent and significant pretreatment factors associated with virological nonresponse to combination therapy in patients with high viral load of genotype 1b [Akuta et al, 2005b]. Therefore, based on the larger numbers of patients, a case-control study was conducted to compare the substitution patterns in aa 70 and/or aa 91 of the core region, between virological non-responders and virological responders who were matched for age, sex, genotype, and viral load, in the present study.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation